Educational emergencies and resilience in intractable conflicts: some reflections on the Israeli reality - Silvia Guetta (Formare, 2023)
In accordance with Witzum and Kotler (2000), since its birth as a state in 1948, Israel has faced military conflicts, years of terrorism, and daily threats. These events have led to the consideration of this reality as a special context for identifying, analyzing, and proposing clinical and educational actions aimed at dealing with trauma caused by wars and terrorism. Some researchers (Bar Tal, 2004; Salomon, 2003) consider the Israeli reality a context within which the characteristics of intractable conflict have developed. A type of conflict that has significant repercussions in the area of perception of reality, construction of society and vision of the future. In addition to examining these aspects, in the last part, the paper analyzes some models of education in emergencies developed over the years in formal and nonformal education contexts.